2017
DOI: 10.1093/sleep/zsx175
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Oral Appliance Therapy Improves Daytime Function and Mood in Upper Airway Resistance Syndrome Patients

Abstract: Efficacy of Oral Appliance for Upper Airway Resistance Syndrome: Randomized, Parallel, Placebo-Controlled Study, NCT02636621.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Summary of characteristic of the included studies is presented in Table 1 . Out of 21 studies,[ 17 19 22 23 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 ] 11 studies compared MAD and CPAP, while 10 studies compared MAD and sham.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Summary of characteristic of the included studies is presented in Table 1 . Out of 21 studies,[ 17 19 22 23 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 ] 11 studies compared MAD and CPAP, while 10 studies compared MAD and sham.…”
Section: Resultsmentioning
confidence: 99%
“…In sequence generation, 70% of studies showed low risk of bias and 30% showed unclear risk of bias. Methods of sequence generation were computer-generated random number,[ 23 38 42 48 52 53 54 56 59 62 65 68 69 73 74 ] block randomization,[ 16 22 43 44 47 60 71 ] and block of four. [ 40 67 ] Many studies did not mention method of sequence generation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations